Silicon-carbon composite negative electrode material and preparation method thereof
By depositing nano-silicon on the interface of porous carbon materials and performing carbon coating treatment, a silicon-carbon composite material is formed, which solves the problem of insufficient electrochemical performance of silicon-carbon composite anode materials in the existing technology and achieves higher cycle stability and energy. density.
Patent Information
- Application Number
- CN202411440790.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The electrochemical performance of existing silicon-carbon composite anode materials has not yet reached the optimal level, especially in terms of cycle stability and energy density.
By depositing nano-silicon onto the interface of porous carbon materials, a silicon-carbon composite material is formed, and the structural strength and conductivity of the material are improved through the carbon coating layer. Specific steps include pretreatment of porous carbon materials, vapor deposition and carbon coating processes to control the amount of silicon deposition and the thickness of the carbon coating layer.
Significantly improve the structural strength, capacity and conductivity of the material, thus improving the cycle stability, fast charging performance and achieving high energy density of lithium-ion batteries.
Smart Images

Figure CN118970019B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a silicon-carbon composite negative electrode material and a preparation method thereof. Background Art
[0002] With the development of new energy and lithium-ion batteries, the shift from gigawatt-hours to terawatt-hours of demand and production has had many impacts on the industry, as well as on technology development and battery requirements. For example, the sustainability of batteries is required, among which lithium batteries are widely used in electric vehicles, so more technical factors such as large battery energy density and driving range are particularly important, and have also become the goal of optimizing battery performance to significantly improve energy density parameters. In the industry roadmap, targets of more than 800 Wh / kg and 350 Wh / kg are not uncommon. In order to achieve these goals, the industry is turning to high-nickel positive electrodes, silicon negative electrodes, and new battery and battery pack designs, in which negative electrode materials are crucial.
[0003] A good anode material must be stable and allow as much lithium as possible to be repeatedly intercalated and deintercalated, thereby maximizing the energy density, power density, and cycle life of the battery. Low resistance and fast lithium ion transport within the anode material are also necessary for high-power applications. The modern lithium-ion battery industry mainly uses graphite. In order to preserve the limited amount of lithium in the encapsulated battery, high-performance lithium batteries need to form a strong solid electrolyte interphase (SEI) film and minimize irreversible lithium compounds on the anode. Lithium ions are "stored" in graphite anode materials by being intercalated in layered carbons such as graphite, adsorbed on hard carbon, and combined with hydrogen atoms in hydrogenated carbon. Mesophase carbon microbeads (MCMB) have a high theoretical capacity of 372 mA h / g and a low potential distribution (0-0.3V vs. Li / Li + ), has become the standard negative electrode material for modern commercial lithium-ion batteries. However, the specific capacity of MCMB is not enough to meet high-demand applications. Materials such as Sn, Sb, Si and Ge "store" charge by reacting with lithium to form alloys. Among them, the theoretical specific capacity of silicon is much higher than that of MCMB and other negative electrode materials, about 4200mAh / g (Li 4.4 Si).
[0004] However, when the silicon-lithium alloy is formed, the volume of silicon expands by 380%. The expansion and contraction of silicon can cause irreversible mechanical damage to silicon-based electrodes. The silicon powder loses electrical contact with the current collector, resulting in the inability of electrons to transfer from silicon to the current collector. The charge balance restricts the positively charged lithium ions from leaving the silicon and moving to the cathode, thus losing the charge and discharge capacity. In addition, new SEI grows on the new surface formed by the silicon rupture, and the generated SEI consumes additional Li. When the lithium in the battery is depleted to a low level, the battery fails. Therefore, how to maintain electrical contact between silicon particles and the current collector and reduce the number of irreversible SEI by reducing the fresh silicon surface in contact with the electrolyte is one of the challenges. To this end, a new generation of silicon-based negative electrode materials has been developed, that is, by depositing nano-silicon into the interior of a porous carbon substrate, the conductivity of silicon is improved through a porous carbon skeleton, and at the same time, the confinement effect brought by nano-silicon and nano-pores buffers the volume expansion of silicon particles. Summary of the invention
[0005] In order to solve the problem that the electrochemical performance of silicon-carbon composite negative electrode materials in the prior art needs to be further improved, the present invention provides a novel silicon-carbon composite material and a preparation method thereof. A carbon material containing at least one of disordered carbon, microcrystalline carbon and crystalline carbon is activated and pore-formed to form a porous carbon material with a specific gravity of 2000-4000 m 2 / g. Silicon is deposited on the interface of porous carbon materials to form a silicon-carbon composite material. Silicon is deposited on the carbon skeleton, so that it can achieve better conductivity and buffer volume expansion, and improve cycle stability. The silicon-carbon composite material provided by the present invention is characterized by XPS: the surface is a material containing Si, Si-O and C-Si-O groups, and the interior is mainly a material containing Si-C groups. To achieve the above purpose, the present invention provides the following technical solutions:
[0006] A silicon-carbon composite negative electrode material is obtained by depositing silicon-containing particles in the pores and surface of porous carbon and then coating the surface with carbon. In the XPS Si 2p spectrum of the silicon-carbon composite negative electrode material, the surface 0.4 Si-Si / S C-Si-O <0.7, material inside: 3 Si-C / S C-Si-O <4; the material surface refers to the XPS spectrum measured before argon ion beam etching, and the material interior refers to the XPS spectrum measured after argon ion beam etching to a depth of 70 nm; S Si-Si It is expressed as the Si 2p peak area around 98±0.5 eV, S C-Si-O is the Si 2p peak area around 102±0.5 ev, S Si-C It is the Si 2p peak area near 101.5±0.5 ev.
[0007] The inventors unexpectedly discovered that the material with the above-mentioned specific XPS Si 2p spectrum has significantly improved structural strength, capacity utilization and conductivity of the material, thereby improving the cycle stability and fast charging performance of the lithium-ion battery assembled with it and achieving high energy density. It is speculated that the possible reason is that when the surface S Si-Si / S C-Si-O <0.4, there is more silicon oxide on the surface, resulting in lower capacity and poor conductivity; when the surface S Si-Si / S C-Si-O When the value is >0.7, on the one hand, there is an over-deposition phenomenon, which leads to a low internal porosity of silicon carbon and cannot effectively buffer the volume expansion, resulting in poor cycle performance. On the other hand, there are large single silicon particles, which leads to poor interface stability and easy expansion and breakage during the cycle, showing poor cycle stability. Si-C / S C-Si-O <3, the uniformity of silicon deposition is poor, pores are blocked and silicon cannot be deposited inside the porous carbon. Si-C / S C-Si-O When >7, more SiC is generated, resulting in poor capacity performance.
[0008] Furthermore, the porous carbon has a specific surface area of 2000-4000 m 2 / g, pore volume of 0.9-1.2 cm 3 / g. In a preferred technical solution of the present invention, the porous carbon is prepared by pyrolysis of a carbon source and then activated. The activation is a two-stage activation, the first activation is water vapor activation, and the second activation is carbon dioxide or metal hydroxide activation (potassium hydroxide and / or sodium hydroxide).
[0009] Preferably, the primary activation is performed by steam activation at 800-950°C, and the pore volume after the primary activation is 0.5-0.7 cm 3 / g; in the secondary activation, carbon dioxide is used as an activator, and the activation temperature is 900-1000 °C; when metal hydroxide is activated, the activation temperature is 700-900 °C; after the secondary activation, the pore volume of the porous carbon is 0.9-1.2 cm 3 / g
[0010] Furthermore, in the silicon-carbon composite negative electrode material, Si accounts for 40-65wt% by weight, and the thickness of the carbon coating layer is 2-10nm.
[0011] The deposition of silicon-containing particles and the carbon coating process are well known in the art. For example, the deposition of silicon is to uniformly deposit silicon-containing particles on the interface of carbon materials by one or more methods such as vapor deposition, vapor infiltration, ALD, electroplating, melt infiltration, sol-gel, and impregnation. The silicon-containing particles contain silicon, oxygen, and carbon, mainly silicon alone, and also chemical bonds between silicon and carbon, and silicon and oxygen. The vapor deposition method is preferred, in which the gas containing the silicon source is treated at a certain temperature to crack it to generate silicon nanoparticles that are adsorbed into the porous carbon pores, so as to achieve amorphous nano-silicon deposition, and the mass ratio of the silicon deposition amount to the porous carbon substrate is close to 1:1.
[0012] The carbon coating process is to introduce carbon-containing gas under inert atmosphere for pyrolysis, and a dense carbon layer is deposited on the surface of the material. The carbon-containing process gas is selected from at least one of methane, ethane, propane, butane, ethylene, propylene, butene, butadiene, acetylene, and propyne. The carbon coating temperature is 500-600°C; the thickness of the carbon coating layer is 3-10nm.
[0013] The present invention also provides a method for preparing the above silicon-carbon composite negative electrode material, comprising the following steps:
[0014] (S1) Pretreatment: The porous carbon is subjected to surface pretreatment at 900-1000° C. by introducing a carbon source gas in a vapor deposition device; the porous carbon is obtained by two activations of the carbon source to form pores, wherein the first activation is water vapor activation and the second activation is carbon dioxide activation or metal hydroxide activation.
[0015] (S2) primary silicon deposition: cooling to 450-500°C, introducing a mixture of silane and inert gas, and controlling the amount of gas introduced so that the amount of silicon deposited accounts for 10-15wt% of the product;
[0016] (S3) Secondary silicon deposition: the temperature is raised to 550-650° C., a mixed gas of silane and inert gas is continuously introduced, silicon deposition is continued, and the gas flow rate is controlled so that the deposition amount of silicon accounts for 40-65wt% of the product;
[0017] (S4) Carbon coating: cooling to 500-600° C., introducing carbon-containing process gas for carbon coating.
[0018] Furthermore, in step (S1), the carbon source gas is C1-3 alkane, and the carbon source gas cracking molecules are small and easy to enter the pores and deposit along the interface. By controlling the carbon source introduction rate to 1-2L / min and the pretreatment time to 1-2h, it is deposited on the internal pore walls of the porous carbon without blocking the pores, thereby achieving graphene surface treatment of the internal carbon walls. Since there are more defects and dangling bonds on the graphene surface, it is easier to adsorb silane gas, so that the heterogeneous deposition of silicon in the subsequent deposition process is greater than the homogeneous deposition.
[0019] Furthermore, in steps (S2) and (S3), the silicon source gas is selected from at least one of monosilane, disilane, dichlorosilane and chlorosilane; and the inert gas is selected from at least one of nitrogen, argon and helium.
[0020] The step (S2) performs relatively low temperature deposition so that the silicon source gas can be deposited more easily inside the porous carbon, and then the temperature is raised to perform relatively high temperature deposition in step (S3) to improve the utilization rate of silicon deposition.
[0021] The present invention achieves a surface 0.4 by regulating the deposition amount and carbon coating. Si-Si / S C-Si-O <0.7, achieved through pretreatment process, deposition amount and deposition temperature: 3 Si-C / S C-Si-O <4.
[0022] Furthermore, the porous carbon is obtained by activating the carbon source twice to form pores and then subjecting it to high-temperature carbonization, which specifically includes the following steps:
[0023] (T1) The carbon source was activated once in the presence of water vapor to obtain a pore volume of 0.5-0.7 cm 3 / g of the first porous carbon;
[0024] (T2) The first porous carbon is subjected to secondary activation, and the activator is carbon dioxide or metal hydroxide (sodium hydroxide and / or potassium hydroxide), and the pore volume is 0.9-1.2 cm 3 / g of a second porous carbon;
[0025] (T3) The second porous carbon is crushed and carbonized in a high temperature furnace to finally obtain porous carbon.
[0026] Furthermore, in step (T1), the carbon source is one or more of coconut shell carbon, asphalt, petroleum coke and resin, which are carbonized by pyrolysis, and the pyrolysis temperature is 700-1000°C; the water vapor activation temperature is 800-950°C.
[0027] Furthermore, in step (T2), when the activator is carbon dioxide, the activation temperature is 900-1000°C; when the activator is a metal hydroxide, the activation temperature is 700-900°C. The purpose of secondary activation is to continue to create micropores on the basis of a larger pore size to form a secondary porous carbon material with a pore structure gradient, which can facilitate the penetration of silane gas in the subsequent silicon deposition process and avoid insufficient silane penetration resulting in poor deposition uniformity inside and outside the particles.
[0028] Furthermore, in step (T1), the pore volume is adjusted by regulating the activation gas flow rate and activation time; in step (T2), when the activator is carbon dioxide, the pore volume is adjusted by adjusting the carbon dioxide gas flow rate and activation time; when the activator is a metal hydroxide, the pore volume is adjusted by adjusting the carbon-base ratio.
[0029] Furthermore, in step (T3), the carbon is crushed to a Dv50 of 5-10 μm, and then carbonized at 1100-1600° C. in an inert atmosphere for 2-5 hours to remove oxygen functional groups on the surface of the porous carbon material and improve the structural strength and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The first cycle voltage-specific capacity curve of Example 1;
[0031] Figure 2 This is the Si 2p peak spectrum analysis of XPS in Example 1. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0033] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0034] X-ray photoelectron spectroscopy (XPS) was performed on a Thermo Scientific ESCALab 250Xi with argon ion beam sputtering for depth profiling (~7 nm min -1 ).
[0035] Preparation Example 1
[0036] (T1) Coconut shell carbon was used as a carbon source and activated once at 800 °C in the presence of water vapor. The activation gas flow rate and activation time were adjusted to obtain a pore volume of 0.6 cm 3 / g of a first porous carbon precursor;
[0037] (T2) The first porous carbon precursor was activated for a second time at 1000 °C in the presence of carbon dioxide, and the activation gas flow rate and activation time were adjusted to obtain a pore volume of 1.1 cm 3 / g of a second porous carbon precursor;
[0038] (T3) The second porous carbon precursor is crushed to a Dv50 of 8 μm, and is heated to 1400° C. in a high-temperature furnace for 2 h under a nitrogen atmosphere to perform carbonization, thereby finally obtaining porous carbon.
[0039] Preparation Example 2
[0040] The other conditions were the same as those in Preparation Example 1, except that step (T2) was changed to: after the first porous carbon precursor and potassium hydroxide were mixed, secondary activation was performed at 800 °C, and the carbon-base ratio was adjusted to obtain a pore volume of 1.1 cm 3 / g of the second porous carbon precursor.
[0041] Comparative Preparation Example 1
[0042] (T1) Coconut shell carbon was used as a carbon source and activated once at 800 °C in the presence of water vapor. The activation gas flow rate and activation time were adjusted to obtain a pore volume of 1.1 cm 3 / g of porous carbon precursor;
[0043] (T2) The porous carbon precursor was crushed to a Dv50 of 8 μm, and then heated to 1400° C. in a high-temperature furnace for 2 h under a nitrogen atmosphere to perform carbonization, thereby finally obtaining porous carbon. That is, compared with Preparation Example 1, the carbon dioxide activation in step (T2) was eliminated.
[0044] Comparative Preparation Example 2
[0045] (T1) Coconut shell carbon was used as a carbon source for secondary activation at 1000 °C in the presence of carbon dioxide. The activation gas flow rate and activation time were adjusted to obtain a pore volume of 1.1 cm 3 / g of porous carbon precursor;
[0046] (T32) The porous carbon precursor was crushed to a Dv50 of 8 μm, and heated to 1400° C. in a high-temperature furnace under a nitrogen atmosphere for 2 h to perform carbonization, thereby finally obtaining porous carbon. That is, compared with Preparation Example 1, the water vapor activation in step (T1) was eliminated.
[0047] Example 1
[0048] (S1) 10 kg of the porous carbon material prepared in Preparation Example 1 was put into a vertical fluidized bed reactor, and 2 L / min of methane gas was introduced at 950° C. and kept warm for 1 hour;
[0049] (S2) After cooling to 450°C, a mixed gas of 5 L / min monosilane gas and 5 L / min nitrogen gas was introduced, and the temperature was kept for 4 hours. The introduction of the mixed gas was stopped. At this time, silicon accounted for 13.2wt% of the obtained material;
[0050] (S3) After the temperature is raised to 550°C, a mixed gas of 5 L / min monosilane and 5 L / min nitrogen is continuously introduced and kept warm for 12 h. At this time, silicon accounts for 51.5 wt% of the obtained material.
[0051] (S4) The temperature was then raised to 600°C, 5 L / min acetylene gas was introduced and kept at this temperature for 2 h before being cooled to room temperature and discharged to obtain the product silicon-carbon composite material. The prepared material was characterized by XPS Si 2p test. Si-Si / S C-Si-O =0.63, material interior: S Si-C / S C-Si-O =3.2. The XPS spectrum of the material is obtained by argon ion beam etching at a depth of 70 nm.
[0052] Figure 1 This is the first cycle voltage-specific capacity curve of the silicon-carbon composite material obtained in Example 1.
[0053] Figure 2 This is the Si 2p peak spectrum analysis of the XPS of the silicon-carbon composite material prepared in Example 1.
[0054] Example 2
[0055] (S1) 10 kg of the porous carbon material prepared in Preparation Example 2 was put into a vertical fluidized bed reactor, and 1 L / min of methane gas was introduced at 900° C. for 2 h;
[0056] (S2) After cooling to 500°C, a mixed gas of 5 L / min monosilane gas and 5 L / min nitrogen gas was introduced, and the mixture was kept at this temperature for 4 h. The introduction of the mixed gas was stopped. At this time, silicon accounted for 13.4 wt% of the obtained material.
[0057] (S3) After the temperature is raised to 650°C, a mixed gas of 5 L / min monosilane and 5 L / min nitrogen is continuously introduced and kept at this temperature for 12 h. At this time, silicon accounts for 51.7 wt% of the obtained material.
[0058] (S4) The temperature was then lowered to 550°C, 5 L / min of methane gas was introduced and kept warm for 4 h before being cooled to room temperature and discharged to obtain the product silicon-carbon composite material. The final material was characterized by XPS Si 2p test. The surface S Si-Si / S C-Si-O is 0.59, the internal S Si-C / S C-Si-O is 3.5.
[0059] Example 3
[0060] Other conditions and operations were the same as those in Example 1, except that in step (S1), methane gas was replaced by ethylene and the holding time was changed to 1.5 h. The final material was characterized by XPS Si 2p test. Si-Si / S C-Si-O is 0.45, the internal S Si-C / SC-Si-O is 3.4.
[0061] Example 4
[0062] Other conditions and operations were the same as those in Example 1, except that in step (S2), the holding time was changed to 5 h. In the product obtained in step (S2), silicon accounted for 14.7 wt %. The final material was characterized by XPS Si 2p test. Si-Si / S C-Si-O is 0.58, the internal S Si-C / S C-Si-O is 3.3.
[0063] Example 5
[0064] Other conditions and operations were the same as those in Example 1, except that in step (S3), the holding time was changed to 14 h, and the product obtained in step (S2) contained 54.2 wt % silicon. The final material was characterized by XPS Si 2p test, and the surface S Si-Si / S C-Si-O is 0.70, the internal S Si-C / S C-Si-O is 3.7.
[0065] Comparative Example 1
[0066] Other conditions and operations are the same as those in Example 1, except that in step (S1), the porous carbon is prepared from Comparative Preparation Example 1. The prepared material was characterized by XPS test. The surface of the material: S Si-Si / S C-Si-O 0.84, material interior: S Si-C / S C-Si-O It is 5.1.
[0067] Comparative Example 2
[0068] Other conditions and operations are the same as those in Example 1, except that in step (S1), the porous carbon is prepared from Comparative Preparation Example 2. The prepared material was characterized by XPS test. The surface of the material: S Si-Si / S C-Si-O 0.54, material interior: S Si-C / S C-Si-O is 4.6.
[0069] Comparative Example 3
[0070] The other conditions and operations are the same as those in Example 1, except that step (S1) is omitted and the porous carbon material of Preparation Example 1 is used to perform steps (S2) to (S4). The material finally obtained is characterized by XPS test. The surface of the material: S Si-Si / S C-Si-O0.27, material interior: S Si-C / S C-Si-O is 2.8.
[0071] Comparative Example 4
[0072] Other conditions and operations are the same as those in Example 1, except that the temperature is 400°C during the first silicon deposition in step (S2). The prepared material was characterized by XPS test. The surface of the material: S Si-Si / S C-Si-O 0.47, material interior: S Si-C / S C-Si-O is 2.6.
[0073] Comparative Example 5
[0074] Other conditions and operations are the same as those in Example 1, except that the temperature is 500°C during the second silicon deposition in step (S3). The prepared material was characterized by XPS test. The surface of the material: S Si-Si / S C-Si-O 0.78, material interior: S Si-C / S C-Si-O is 2.8.
[0075] Comparative Example 6
[0076] Other conditions and operations are the same as those in Example 1, except that the temperature is 800°C during the second silicon deposition in step (S3). The prepared material was characterized by XPS test. The surface of the material: S Si-Si / S C-Si-O 0.72, material interior: S Si-C / S C-Si-O is 4.1.
[0077] Comparative Example 7
[0078] Step (S1) is the same as in Example 1, followed by:
[0079] (S2) After cooling to 500°C, a mixed gas of 5 L / min monosilane gas and 5 L / min nitrogen gas was introduced, and the mixture was kept warm for 16 h. The introduction of the mixed gas was stopped. At this time, silicon accounted for 52.4wt% of the obtained material.
[0080] (S3) The temperature was then raised to 600 °C, 5 L / min acetylene gas was introduced and kept at this temperature for 2 h before cooling to room temperature and discharging to obtain the product silicon-carbon composite material. The prepared material was characterized by XPS Si 2p test. The surface S Si-Si / S C-Si-O =0.77, material interior: S Si-C / S C-Si-O =2.7.
[0081] Application Examples
[0082] Performance test of silicon-carbon composite material as negative electrode material for lithium batteries
[0083] The silicon-based materials obtained by the present invention are tested for electrochemical performance according to the following method: silicon-carbon material, SuperP, carbon nanotubes and carboxymethyl cellulose and styrene-butadiene rubber composite binder are mixed in a mass ratio of 80:9.8:0.2:10 to form a slurry (the mass ratio of CMC and SBR is 1:1), and the slurry is applied to a copper foil with a 200 μm thick scraper, dried in a drying room, and placed in a vacuum dryer for 12 hours to prepare a silicon-based negative electrode plate; then, metallic lithium is used as a counter electrode, polyolefin is used as a diaphragm, 1 mol / LLiPF6 (the solvent is a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) is used as an electrolyte, 2% of VC and 5% of FEC are added to the electrolyte, and button batteries are assembled in an argon atmosphere in a Braun inert gas glove box in Germany.
[0084] The battery assembled above was charged and discharged on a LAND charge and discharge tester, with a charge and discharge range of 50 mV to 1.5 V and a compaction density of 1.1 g / cm 3 After three charge and discharge cycles at a current density of 0.1 C (1 C = 1500 mA / g), rate charge and discharge tests were carried out at a rate of 1C.
[0085] According to the same method, the silicon-carbon composite materials obtained in the examples of the present invention and the comparative examples were used as negative electrode materials to assemble button-type lithium batteries, and the electrochemical test results are listed in Table 1.
[0086] Table 1 Electrochemical performance test of silicon-carbon composite materials
[0087] .
Claims
1. A method for preparing a silicon-carbon composite negative electrode material, characterized in that: The following steps are involved: (S1) Pretreatment: The porous carbon is subjected to surface pretreatment at 900-1000° C. by introducing carbon source gas in a vapor deposition device; The porous carbon is obtained by two activations of the carbon source, wherein the first activation is water vapor activation and the second activation is carbon dioxide activation or metal hydroxide activation; (S2) primary silicon deposition: cooling to 450-500°C, introducing a mixture of silane and inert gas, and controlling the amount of gas introduced so that the amount of silicon deposited accounts for 10-15wt% of the product; (S3) Secondary silicon deposition: the temperature is raised to 550-650° C., a mixed gas of silane and inert gas is continuously introduced, silicon deposition is continued, and the gas flow rate is controlled so that the deposition amount of silicon accounts for 40-65wt% of the product; (S4) Carbon coating: cooling to 500-600° C., introducing carbon-containing process gas for carbon coating; In the XPS Si 2p spectrum of the silicon-carbon composite negative electrode material, the surface 0.4 Si-Si / S C-Si-O < 0.7, material inside: 3 Si-C / S C-Si-O < 4; the material surface refers to the XPS spectrum measured before argon ion beam etching, and the material interior refers to the XPS spectrum measured after argon ion beam etching to a depth of 70 nm; S Si-Si It is expressed as the Si2p peak area around 98±0.5 eV, S C-Si-O is the Si 2p peak area around 102±0.5 ev, S Si-C It is the Si2p peak area near 101.5±0.5 ev. 2. The preparation method according to claim 1, characterized in that: The specific surface area of the porous carbon is 2000-4000 m 2 / g, pore volume of 0.9-1.2 cm 3 / g.
3. The preparation method according to claim 1, characterized in that: The first activation is water vapor activation at 800-950℃. The pore volume after the first activation is 0.5-0.7 cm 3 / g; in the secondary activation, carbon dioxide is used as an activator, and the activation temperature is 900-1000 °C; when metal hydroxide is activated, the activation temperature is 700-900 °C; after the secondary activation, the pore volume of the porous carbon is 0.9-1.2 cm 3 / g.
4. The preparation method according to claim 1, characterized in that: In the silicon-carbon composite negative electrode material, Si accounts for 40-65wt% by weight, and the thickness of the carbon coating layer is 2-10 nm.
5. The preparation method according to claim 1, characterized in that: In step (S1), the carbon source gas is C1-3 alkane, and the pretreatment time is 1-2h; and / or In steps (S2) and (S3), the silane is selected from at least one of monosilane, disilane, dichlorosilane and chlorosilane; and the inert gas is selected from at least one of nitrogen, argon and helium.
6. The preparation method according to claim 1, characterized in that: The porous carbon is obtained by activating the carbon source twice to form pores and then subjecting it to high-temperature carbonization, comprising the following steps: (T1) The carbon source was activated once in the presence of water vapor to obtain a pore volume of 0.5-0.7 cm 3 / g of the first porous carbon; (T2) The first porous carbon is activated twice, and the activator is carbon dioxide or metal hydroxide to obtain a pore volume of 0.9-1.2 cm 3 / g of a second porous carbon; (T3) The second porous carbon is crushed and carbonized in a high temperature furnace to finally obtain porous carbon.
7. The preparation method according to claim 6, characterized in that: In step (T1), the carbon source is one or more of coconut shell carbon, asphalt, petroleum coke and resin, which are carbonized by pyrolysis, the pyrolysis temperature is 700-1000°C; the steam activation temperature is 800-950°C; and / or In step (T2), when the activating agent is carbon dioxide, the activation temperature is 900-1000°C; when the activating agent is a metal hydroxide, the activation temperature is 700-900°C; and / or In step (T3), the particles are crushed to a Dv50 of 5-10 μm and then carbonized at 1100-1600° C. in an inert atmosphere for 2 h.
Citation Information
Patent Citations
Silicon-carbon composite material and preparation method thereof, lithium ion battery and electronic equipment
CN116504986A